Task and Feedback-Based on English learning to Enhance Student Character - Kartakusumah, Berliana; Sya, Mega Febriani; Maufur, Mustolah (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Task-based English learning is also an essential consideration for strengthening students’ character. Nevertheless, not many teachers make the task essential to the learning process. The tasks consider the situation of the condition and the student’s psychological state. Tasks are in the form of homework as individuals or groups. This study aims to identify an overview of students’ perception of the task model given by teachers in English classes and their feedback. The research was conducted at elementary schools in West Java and Bangka Belitung provinces, obtained from 116 students’ elementary schools, purposive sampling—data retrieval technique using a questionnaire. Data analysis uses descriptive statistics with stages of collecting, compiling, processing, presenting, and analyzing numerical data to provide a regular, concise, and clear picture of a symptom or event. The results showed that students’ perceptions varied with the tasks given. It shows a tendency to one type of task, and almost all students considered that the teacher did not always give feedback on the task given. These tasks can take the form of group tasks and individual tasks. It was concluded that each individual showed different response patterns in exploring foreign languages.